Soil Transmitted Helminths and Schistosomiasis in Adamawa Northern Senatorial District, Nigeria - Mathew, Yaro; Wilson, Ataitiya; Abdullahi, Mubarak; Saidu, Ali (African Multidisciplinary Journal of Sciences and Artificial Intelligence, 2025)
Helminthiasis is a parasitic infection known to infect low-income population group and people with poor personal hygiene worldwide. Helminths (Worms) such as roundworm, hookworm, whipworm and the flat worms (schistosome) are among others that causes heminthiasis. Infections with these worms results to mild, chronic and severe illness especially in an endemic area. This study reports the prevalence of soil-transmitted helminthiasis and schistosomiasis in Adamawa Northern Senatorial District that are made up of five Local Areas namely, Maiha, Mubi North, Mubi South, Michika and Madagali Local Government Areas out of which two communities where sampled from each LGA. Normal saline direct wet preparation, formol-ether concentration and Polymerase Chain Reaction (PCR) techniques were used to analyze stool samples. Centrifugation and filtration technique were used for urine analysis, Out of 2,808 stool and urine samples examined from 1,404 participants, an overall prevalence of 565 (40.2%) were recorded. Out of these, soil-transmitted Helminthiasis account for 239 (17.0%) while Schistosomiasis infections was 326 (23.2%) respectively. The highest prevalence of Soil-transmitted helminthiasis by community was recorded in Bororo (23.6%) and lowest in Pakka (12.5%) communities. While highest and lowest prevalence of Schistosomiasis were observed in Pakka and Kuda with 30.0% and 15.7% respectively and there was statistical significant difference (p<0.05) between the two infections. The study further revealed that farmers (27.1%) had highest infection with STH while students (38.2%) had more infections with Schistosomiasis and there was no significant statistical differences at (p>0.05). Differences were observed between STHs and Schistosomiasis in relation to occupation. The distribution of each parasite during the study also revealed that, high prevalence (18.5%) of S. haematobium was recorded while Strongyloide stercoralis had the lowest prevalence (2.9%) with significant differences at (P<0.05). Total co-infection of 5.2% was also recorded for STHs and Schistosomiasis. Similarly, analysis of stool sample using PCR further revealed the presence of A. lumbricoides, Hookworms and T. trichiura. Therefore, the findings has reveal the presence of helminthiasis to high among low income participants in the study area.